Examining the dynamic relationships between exposure tasks and cognitive restructuring in CBT for SAD: Outcomes and moderating influences. (April 2016) - Hawley, Lance L.; Rector, Neil A.; Laposa, Judith M.
Highlights: Bivariate latent difference score longitudinal models indicated that the frequency of both exposure and thought record skill use led to subsequent symptom alleviation throughout CBT treatment for social anxiety disorder. The longitudinal association of exposure frequency and subsequent symptom alleviation is greater than the longitudinal association of thought record frequency and subsequent symptom alleviation. Pre-treatment perfectionism was associated with longitudinal changes in skill use during CBT treatment for social anxiety disorder—greater initial skill use was followed by reduced subsequent skill use. Abstract: Meta-analyses indicate that cognitive behavioral therapy (CBT) for social anxiety disorder (SAD) leads to substantial symptom alleviation. Although there is an emphasis on engaging in exposure and cognitive restructuring during treatment, the longitudinal relationship between skill use and symptom alleviation is not well understood. Furthermore, treatment response may be attenuated by pre-existing patient vulnerabilities. This study examined the longitudinal association of skill use (i.e. exposure (EX), thought record use (TR)), symptom reduction and the potential moderating influence of perfectionism during a 12-session, manual-based CBT for SAD intervention for 100 patients (51% female) meeting DSM-IV criteria for SAD. Results obtained from Latent Difference Score (LDS) models indicated that the frequency of both EX and TR skill use led to subsequent symptom alleviation; however, this varied based on the type of skill used. Further, although both EX and TR interventions were associated with subsequent symptom reduction, the association of EX and subsequent symptom alleviation was greater than the association of TR and subsequent symptom alleviation. Finally, higher pre-treatment perfectionism was associated with greater initial skill use, followed by significantly reduced skill use in later sessions. These preliminary results suggest that perfectionistic individuals demonstrate differential engagement in EX and TR interventions during treatment.